Встановлення узгодженності результатів експертного оцінювання - Пономарьов, А. В. (ХНУРЕ, 2021)
The approach to solving the problem of checking the consistency of experts' opinions when considering the tasks of expert evaluation is considered. To do this, use different indicators. The most used of these is the concordance factor. But the results of calculations show some of its shortcomings. A modified concordance coefficient or Spearman's rank correlation coefficient is recommended. These coefficients are also suitable for use in algorithms for constructing ranked lists of any objects of comparison using a four-point scale, as well as in professional selection procedures and in pedagogical qualimetry.